2007
DOI: 10.1002/jmv.20796
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of adenovirus species B and C viremia by real‐time PCR in adults and children undergoing stem cell transplantation

Abstract: Adenovirus infection during stem cell transplantation is associated with high morbidity and mortality. Adenovirus species B and C have been the main causes for these infections; however, epidemiological details about the species are still unclear. To clarify the contributions of species B and C adenovirus, the DNA was tested serially by quantitative real-time PCR in peripheral blood, stool and urine of 32 patients (16 adults and 16 children) undergoing stem cell transplantation. Adenovirus species B viremia wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 32 publications
1
20
1
Order By: Relevance
“…For example, in the transplant unit of St. Anna Children's Hospital, Vienna, Austria, HAdV species C accounts for about 80% of all adenoviral infections observed, and similar numbers were also reported from other transplant centers in different geographic regions (43,69,(71)(72)(73). Sequential or concomitant coinfections with different adenoviruses from the same or different species are quite commonly observed in both the immunocompetent and immunocompromised patient settings (74)(75)(76) and may thus play a role in the generation of recombinant HAdV types.…”
Section: Prevalence Of Hadv Species and Typesmentioning
confidence: 57%
“…For example, in the transplant unit of St. Anna Children's Hospital, Vienna, Austria, HAdV species C accounts for about 80% of all adenoviral infections observed, and similar numbers were also reported from other transplant centers in different geographic regions (43,69,(71)(72)(73). Sequential or concomitant coinfections with different adenoviruses from the same or different species are quite commonly observed in both the immunocompetent and immunocompromised patient settings (74)(75)(76) and may thus play a role in the generation of recombinant HAdV types.…”
Section: Prevalence Of Hadv Species and Typesmentioning
confidence: 57%
“…No evidence of nonreplicating adenoviral DNA from any other species was identified in these samples. It remains possible that other serotypes of adenovirus form latent or persistent infections in other tissues, such as species B serotypes in kidney (25,56,60), lung (35), or possibly brain (32), but because of different tissue tropism, these viruses were not detected in tonsil and adenoid tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Four of these patients had localised HAdV dis- ease, such as haemorrhagic cystitis ( Table 2, patient numbers 9 and 19), gastroenteritis (patient 20) or diarrhoea which was clinically associated with GvHD (patient 24). In one of these patients HAdV may have contributed to the aetiology of pneumonia although this was clinically diagnosed as aspiration pneumonia (patient 18). Four examples of HAdV load kinetics are shown in supplementary Fig.…”
Section: Hadv Blood Loadsmentioning
confidence: 95%
“…9 While the incidence of HAdV infections in paediatric SCT recipients varies widely between 8% and 50% in different studies, HAdV related mortality is consistently reported to be about 5% (3-7%). 10,11,[16][17][18][19][20][21] Since high HAdV blood loads are associated with the development of HAdV disseminated disease in paediatric patients, HAdV DNAaemia is monitored after allogeneic SCT in many paediatric SCT centres. 10,15,18,20 In contrast, data concerning the incidence of HAdV related disease and mortality in adults are limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation